(3OSJhQ GdejbGJ aj Yde GdChbGJs - (3GdHQWSj, eMeO Hf SYjO Hf Ydjs
(3ChdgG (B:s
(3HSe Gddg agPg ebOeI SgdI GdYHGQI hGdeCNP aj Yde Gdadc GdeSei HGdgjFI jYde efgG GhbGJ GdUdhGJ hSejJgG hQJHJgG Ydi JSYI CHhGH ; GdHGH GdChd aj aVd gPG GdYde hGdJQZjH aj eYQaI GdChbGJ s
(3BNQgG (B:s
(3GdaUd GdJGSY aj eYQaI GdeWGdY GdadcjI hGdeWGdY GdHdOjI aUd hEf SbWJ GdOGjQ YfO fUa Gddjd aj GdOGjQ Yfg GdTeS NQL dc fUa bhS Gddjd GdKGfj hGddg CYde (B, (3hGYde Cf eWGdY GdZQhH eKGd Pdc Jchf GdTeS aj HQL GdCSO aJYO Jbhd s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs